EVALUATING CURRENT ASSESSMENT AND TREATMENT OF DELIRIUM BY UK PALLIATIVE CARE PHYSICIANS. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Elliot, Victoria; Lowe, Emma; Owen, Rebecca; Adams, Charlotte; Sheils, Rachel
Abstract : Background: Delirium is a common condition seen in all areas of clinical medicine, particularly in patients with advanced disease. Its prevalence is expected to rise from the current level of 28-90% with the use of more aggressive anti-cancer treatments. The condition is often under recognised but can be distressing for both patients and their relatives. Aims: The objective of this study was to establish how palliative care physicians in the UK assess and treat delirium (including drug treatment). Methods: A questionnaire was developed and sent via the Association of Palliative Medicine to all UK members. The questionnaire contained 10 questions with multiple choice answers but also allowed space for free text. Results: The results highlighted that currently physicians most commonly use no screening tools for diagnosing delirium (35%). They also highlighted that when treating delirium, conservative measures, such as quiet environment and reassurance, are opted for first, as well as identifying and treating reversible causes. However, when drug treatments are required haloperidol is the most popular choice (88.1%). Conclusions: There is current consensus amongst surveyed UK palliative care physicians that conservative management of delirium should be used prior to medications, and that all reversible causes should be investigated. When drug treatment is required Haloperidol is the most popular drug which is in keeping with current NICE guidance. Recommendations for broader research include a screening tool for distress that could be validated in a palliative care population. It is also recognised that there is a lack of high quality evidence about which drugs to use when trying to restore cognitive function in palliative care patients. However, it may be that we should consider extrapolating the evidence from the NICE guidance to our patients, given the characteristics of the patients in the studies included.